Small incisions still require great anesthesia: anesthesiology techniques to enhance recovery in robotic coronary bypass grafting - Hoogma, Danny Feike; Oosterlinck, Wouter; Rex, Steffen (Annals of Cardiothoracic Surgery, 2024)
Robotic coronary artery bypass grafting (CABG) has emerged as a promising minimally invasive surgical technique for the treatment of coronary artery disease. This paper provides an in-depth analysis of the anesthetic management for robotic CABG. Challenges associated with robotic CABG are discussed and various anesthetic techniques, perioperative elements and pain management modalities that can contribute to enhanced patient recovery are explored.